1948
DOI: 10.1021/jo01164a006
|View full text |Cite
|
Sign up to set email alerts
|

1-Dodecanesulfinic Acid

Abstract: In connection with a study of aliphatic sulfinic acids as activators for Redox type polymerization (1) we have had occasion to prepare for the first time a pure crystalline aliphatic sulfinic acid, 1-dodecanesulfinic acid. Autenrieth (2) has reported the isolation of pure benzenesulfinic acid, but he found that the aliphatic acids were unstable, and did not accomplish their isolation. 1-Dodecanesulfinic acid appears to be considerably more stable than the lower alkanesulfinic acids but on standing for two mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

1965
1965
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 4 publications
1
27
0
Order By: Relevance
“…(1 1) and the degree of polymerization is l/E = R,/Rv =-(2kt k~/kv)'"[TU]"'[HzO~]~"[AN] (12) Equations (11) and, (12) are in good agreement with the experimental The initiation reaction should be studied in more detail, but it results. seems likely that above polytnerization scheme is appropriate.…”
Section: Nhsupporting
confidence: 55%
See 1 more Smart Citation
“…(1 1) and the degree of polymerization is l/E = R,/Rv =-(2kt k~/kv)'"[TU]"'[HzO~]~"[AN] (12) Equations (11) and, (12) are in good agreement with the experimental The initiation reaction should be studied in more detail, but it results. seems likely that above polytnerization scheme is appropriate.…”
Section: Nhsupporting
confidence: 55%
“…Sulfinic acids are known, in general, for their tendency to decompose. 12 Formamidine sulfinic acid, however, was isolated after the reaction of Hz02 and thiourea at low temperature (OOC.) in aqucous so1uti0n.l~ Therefore, it must be considered in our caae as well that sulfinic acid is formed, and that the acid initiates the polymerization of acrylonitrile.…”
Section: Discussionmentioning
confidence: 99%
“…24 We have observed that under physiological conditions only small amounts of our peptide sulfinamides are converted to the corresponding sulfinic acids after 26 h. Because of the relatively longer half-life of sulfinic acid formation, the reduction of sulfinic acids to thiols is not considered to be a probable pathway. 52,53 This is supported by the fact that no significant sulfinic acid formation is observed in the presence of DTT.…”
Section: ■ Discussionmentioning
confidence: 83%
“…Detailed procedures for the synthesis of the sulfide-sulfinate salts 16 [e.g. sodium 4-(tert-butyldithi~)butanesulfinate~~"] and of the 4-rnercaptobutanesul~nic acid, disodiurn…”
Section: Nucleophilic Cleavage Of the Sulfur-sulfur Bond In Thiosumentioning
confidence: 99%